Bird mola (maternity blouse) - Unidentified artist (Colorado State University. Libraries, 1990)
Maternity blouse worn by a mannequin.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton.
Outfit mola.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama